PENGARUH PRODUKSI, KONSUMSI DAN KURS DOLLAR AMERIKA SERIKAT TERHADAP VOLUME EKSPOR TEMBAKAU INDONESIA TAHUN 1993-2019 - Sita Paramananda Putri, Ni Putu; Sutrisna, I Ketut; Sutrisna, I Ketut; Wenagama, i Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323], 2022)
Tobacco is a plant which is the main raw material in the cigarette industry which has economic value and is a source of foreign exchange for the country. Tobacco is one of the important trade commodities in the world. Indonesia's tobacco export activities have fluctuated, it is important to study and analyze the factors that affect the volume of Indonesian tobacco. The purpose of conducting this research is to see the effect of the independent variables of this study, namely production, consumption and the US dollar exchange rate on the volume of Indonesian tobacco exports in 1993-2019. The research was conducted in Indonesia. The type of data used is quantitative data with secondary data. Data collection was carried out through non-participant observation methods, which came from books, notes and reports from related sources or agencies. The analysis technique used is multiple linear regression using time series data from 1993 - 2019. The results showed that the variables of production, consumption and the US dollar exchange rate had a simultaneous and significant effect on the volume of Indonesian tobacco exports. The results of the T test research indicate that the production variable has a positive and insignificant effect on the volume of Indonesian tobacco exports. Consumption has a negative and significant effect on the volume of Indonesian tobacco exports and the US dollar exchange rate has a positive and significant effect on the volume of Indonesian tobacco exports